Kabupaten Pesisir Pengembangan Diri Seni Tari Di SMAN 1 Ranah Pesisir Selatan - Aulia Fatmawati; Susmiarti Susmiarti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The aim of this research is to describe and reveal the presentation form of Rampak Sapinggan dance by Sanggar Sarunai Tonic in Payakumbuh Barat sub-district, Payakumbuh City This type of research is qualitative research with descriptive method The main instrument used is the researcher himself and supported by supporting instruments such as writing tools, cameras, and smartphones Data collection techniques are carried out by means of literature study, observation, and interviews Data analysis techniques are by means of data collection, data reduction, data presentation, and conclusion drawing. The research results show that Tari Rampak Sapinggan is one of the Creative Dances developed based on the basic movements of dance and Minang silek movements Tari Rampak Sapinggan is a non-representational dance, which means it does not depict anything Tari Rampak Sapinggan has a sequence of movements that starts from: sambah movement, tapuak galembong, ayun babuai, maarak or manjapuik, sanduak mancukam, lenggok baayun, baganjua maju, bajombo-jombo, basiang tagak, kibeh, baganjua suruik batanam, salingkuang korong, mambori sambah The number of dancers is 5 or odd, the floor pattern uses straight and curved lines The accompanying music uses traditional Minangkabau music such as Gandang, Talempong, and Sarunai Makeup uses beautiful makeup for women and handsome makeup for men Men's costumes wear rang mudo shirts, destar, galembong, and sasampiang, while women wear kurung clothes, songket skirts.